2011
DOI: 10.1097/jcn.0b013e3181f1e3bd
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy in Acute Coronary Syndromes

Abstract: The care of cardiovascular patients experiencing a myocardial infarction (MI) has evolved from simple bed rest and relief of pain to complex interventions and multiple medications that target both the short- and long-term risks associated with atherosclerosis and ischemia. Even the terminology has changed, from MI to acute coronary syndromes (ACSs). The term, acute coronary syndrome, refers to the clinical symptoms resulting from acute myocardial ischemia; it encompasses unstable angina, non-ST-elevation MI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Our findings are supported by the evidence whereby such interventions have been delivered because they are beneficial for cardiac stability and minimizing of frequent CAD attacks [24]. Education regarding lifestyle factors has been found as an essential part of the discharge process [12,27]. Several studies on cardiac rehabilitation for CAD patients suggested that, it is imperative that patients receive proper medical management of coronary risk factors and support for the adoption of a healthy lifestyle [28].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our findings are supported by the evidence whereby such interventions have been delivered because they are beneficial for cardiac stability and minimizing of frequent CAD attacks [24]. Education regarding lifestyle factors has been found as an essential part of the discharge process [12,27]. Several studies on cardiac rehabilitation for CAD patients suggested that, it is imperative that patients receive proper medical management of coronary risk factors and support for the adoption of a healthy lifestyle [28].…”
Section: Discussionsupporting
confidence: 71%
“…Among several efforts underway to search for innovative strategies to strengthen the workforce, the major responsibility falls on advanced practice nurses due to an increasing demand for better chronic disease management and improved health care efficiency for patients at a great extent [11]. The nurses' caring role as a counselor and educator during an acute CAD event has been found to be critical for helping patients understand complex therapies involved in treating ACS and developing a plan that fosters medication adherence so as to ensure safety and improved outcomes [12]. It was further added that nurse’s objectives for the discharge of CAD patients included preparation of a patient to return to usual activities.…”
Section: Introductionmentioning
confidence: 99%
“…This has been done through specialised clinics and programmes in primary care, worksites, and cardiac rehabilitation centres 16 , 17 . Provision of education on complex therapies in treating CAD, counselling on diet and lifestyle for risk factors modification and promotion on cardiac rehabilitation skills are among nursing roles delivered to patients with CAD 14 . A systematic review of randomised controlled trials revealed that nursing interventions (NI) for CAD patients have a beneficial impact on blood pressure (BP), lipids, physical activity, dietary intake, cigarette smoking, weight loss, healthcare utilisation, mortality, quality of life, and psychosocial outcomes.…”
Section: Nurses' Roles and Impact In Caring For Cad Patientsmentioning
confidence: 99%
“…The modern treatment of CAD depends on the nature of coronary artery blockage or damage. These include vascular interventions such as percutaneous intervention (PCIs) (coronary stents and balloon angioplasty), coronary artery bypass graft (CABG), and pharmacological therapy 13,14 . Patients have also benefited and improved their quality of life by attending cardiac rehabilitation programmes 15 .…”
Section: Introductionmentioning
confidence: 99%